Polyvinyl Alcohol/Sodium Alginate/Collagen ( PVA / SA /Col) Hydrogel Beads: Preparation of a Novel Double‐Layer Network Interpenetrating Hydrogel Material and Evaluation of Tannic Acid Adsorption Properties - Yan, Ge; Chen, Qifeng; Zhang, Lixin; Wang, Yunjia (Polymer engineering and science, 2025)
This study presents a reusable adsorbent material for industrial wastewater treatment. Double‐network interpenetrating gel beads were prepared via condensation reaction and hydrogen bonding between sodium alginate and collagen, combined with PVA and ion crosslinking. The addition of collagen enhanced the equilibrium swelling ratio, strengthened the double‐network structure, and increased adsorption sites. Optimal adsorption of tannic acid occurred at a collagen/PVA mass ratio of 1:2, achieving a maximum capacity of 261.53 mg/g and a removal rate of 78.46%. Influenced by multiple factors, the adsorption process followed pseudo‐second‐order kinetics, indicating chemisorption dominance. The beads maintained good adsorption capacity and structural stability over four adsorption–desorption cycles, demonstrating excellent reusability.